The function of Drosophila larval class IV dendritic arborization sensory neurons in the larval-pupal transition is separable from their function in mechanical nociception responses. - Hannah E Brown; Trishna Desai; Allison J Murphy; Harshida Pancholi; Zachary W Schmidt; Hannah Swahn; Eric C Liebl (PLoS ONE)
The sensory and physiological inputs which govern the larval-pupal transition in Drosophila, and the neuronal circuity that integrates them, are complex. Previous work from our laboratory identified a dosage-sensitive genetic interaction between the genes encoding the Rho-GEF Trio and the zinc-finger transcription factor Sequoia that interfered with the larval-pupal transition. Specifically, we reported heterozygous mutations in sequoia (seq) dominantly exacerbated the trio mutant phenotype, and this seq-enhanced trio mutant genotype blocked the transition of third instar larvae from foragers to wanderers, a requisite behavioral transition prior to pupation. In this work, we use the GAL4-UAS system to rescue this phenotype by tissue-specific trio expression. We find that expressing trio in the class IV dendritic arborization (da) sensory neurons rescues the larval-pupal transition, demonstrating the reliance of the larval-pupal transition on the integrity of these sensory neurons. As nociceptive responses also rely on the functionality of the class IV da neurons, we test mechanical nociceptive responses in our mutant and rescued larvae and find that mechanical nociception is separable from the ability to undergo the larval-pupal transition. This demonstrates for the first time that the roles of the class IV da neurons in governing two critical larval behaviors, the larval-pupal transition and mechanical nociception, are functionally separable from each other.